Enhanced dimensional stability and mechanical properties of SBR/EVA foam by a scaffold structure constructed in the bubble cavity-wall. (8th September 2021) - Ji, Zhanyou; Ma, Jianzhong; Guo, Xiaojing; Wu, Yingke; Ma, Zhonglei; Qin, Jianbin; Shao, Liang
Abstract: The poor dimensional stability of rubber foam directly restricts its industrialization. Hence, a scaffold structure was constructed by controlling zinc oxide (ZnO) particles with a small amount of bisphenol-A epoxy resin (EP), which effectively improved the dimensional stability and made it have a promising application prospect. The scaffold structure has controlled ZnO particles densely and evenly distributed in the bubble cavity-wall of styrene butadiene rubber/ethylene vinyl acetate (SBR/EVA) foam. The construction of the scaffold structure was ascribed to EP with high N2 -affinity and strong infiltration to ZnO particle based on cell nucleation in the cavity at the melt−nucleator interface. The construction mechanism and the effect of the scaffold structure on dimensional stability and mechanical property of SBR/EVA foams were investigated by scanning electron microscopy, energy disperse spectroscopy and X-ray diffraction. Compared with SBR/EVA foam, the shrinkage of SBR/EVA foam with the scaffold structure was reduced by 19.4%. The rigidity increased by 59.8% and decreased the toughness by only 3.87% at 3 phr EP content. And its compressive stress (60%) was about 8 times that of SBR/EVA foam. Meanwhile, the ZnO particles were densely and evenly distributed in the bubble cavity-wall that can reinforce the flame retardant of SBR/EVA foams. Graphical abstract: Image 1 Highlights: A scaffold structure has been constructed by blending epoxy resin (EP) and ZnO. ZnO particles were densely and evenly distributed in the bubble cavity-wall by EP. A scaffold structure was ascribed to EP with strong infiltration based on cavity model. The shrinkage of SBR/EVA foam with the scaffold structure reduced by 19.4%. The rigidity of SBR/EVA foam with the scaffold structure increased by 59.8%.